2021
DOI: 10.3390/s21217157
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Water Level in Urban Streams under Bad Weather Conditions

Abstract: Flood control and water resources management require monitoring the water level in rivers and streams. Water level measurement techniques increasingly consider image processing procedures. Most of the systems use a staff gauge to support the waterline detection. However, these techniques can fail when applied to urban stream channels due to water undulation, debris on the water surface, and traces of rain captured by the camera, and other adverse effects on images can be quite dramatic on the results. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Regarding the contactless methods, although ultrasonic sensors are easy to install, they have been shown to be problematic when examining turbulent water [6], which usually happens during flooding events in volcanic islands' water channels [3]. As a result, image-based sensors were found to be suitable for monitoring the water channels in these locations, presenting a low installation and maintenance cost [7]. However, satellite images lack enough spatial and temporal resolutions, particularly for narrow water streams [8], while the use of unmanned vehicles is likely not to be suitable for small urban areas [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the contactless methods, although ultrasonic sensors are easy to install, they have been shown to be problematic when examining turbulent water [6], which usually happens during flooding events in volcanic islands' water channels [3]. As a result, image-based sensors were found to be suitable for monitoring the water channels in these locations, presenting a low installation and maintenance cost [7]. However, satellite images lack enough spatial and temporal resolutions, particularly for narrow water streams [8], while the use of unmanned vehicles is likely not to be suitable for small urban areas [9].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is particularly important in cases or areas where establishing a stage-discharge rating curve is difficult, when possible at all. Research reported on image-based hydrological monitoring tends to either focus on Large Scale Particle Image Velocimetry (LS-PIV) to compute discharge [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], on discharge measurements using machine learning [29], on flood detection from surveillance cameras [30][31][32][33], or, on the stage measurement itself [2,[34][35][36][37][38][39][40][41][42][43] from which discharge is often calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. (2019) and Azevedo and Brás (2021) developed monitoring systems using a single infrared camera to mitigate the visibility issue and image quality. The proposed method by Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method by Zhang et al (2019) provided comparable accuracy to the existing float-type gauges. Average accuracy of 1.8 cm for the daytime and 2.8 cm for the nighttime measurements were determined by Azevedo and Brás (2021). Marker points and recognizable structures such as buildings, concrete walls, rocks, ground control points and even the temporal texture of the changing water surface are alternative to staff gauge for detecting and obtaining water line around the monitoring area (Eltner et al, 2018;Leduc et al, 2018;Young et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation